Increasing the Activity of Sugarcane Sucrose Phosphate Synthase Enhanced Growth and Grain Yields in Transgenic Indica Rice - Mulyatama, Reza Anugrah; Neliana, Intan Ria; Sawitri, Widhi Dyah; Sakakibara, Hitoshi; Kim, Kyung-Min; Sugiharto, Bambang (MDPI, 2022)
Sucrose is the primary form of mobile photoassimilates, and its level is regulated by sucrose-phosphate synthase (SPS) in plants. Increasing in the SPS activity was accompanied by an increase in sucrose accumulation. This study was designed to examine the effect of the overexpression sugarcane SoSPS1 gene on sucrose metabolizing enzymes, growth, and grain yield of indica rice. The SoSPS1 gene was constructed in a binary vector under the control of a rice ubiquitin promoter and transformed into indica rice using an Agrobacterium vector. Five lines of transgenic rice were selected to develop homozygous transgenic lines and used for analysis. The overexpression of the SoSPS1 gene significantly increased the transcript and protein levels, followed by increasing in SPS activity and sucrose content in the leaves of the transgenic rice lines. Moreover, the activity of soluble acid invertase (SAI) was elevated rather than sucrose synthase (SuSy) in the transgenic lines. The increase in the sucrose-degrading enzymes leads to an increase in plant growth and development. The plant height and number of tillers were significantly higher in the transgenic line compared to non-transgenic (NT) rice. In addition, the amylose content, the number of seeds per panicle, and the weight of 1000 grains of seed, including dry biomass weight, were increased in the transgenic lines. The results indicated that enhancement of SPS activity, as well as sucrose content, provides a higher carbon partitioning for higher growth and productivity of the transgenic rice lines.